P2X7 Receptor Triggers Lysosomal Leakage Through Calcium Mobilization in a Mechanism Dependent on Pannexin-1 Hemichannels - Santos, Stephanie Alexia Cristina Silva; Persechini, Pedro Muanis; Henriques-Santos, Bianca Monteiro; Bello-Santos, Victória Gabriela; Castro, Newton G.; Costa de Sousa, Júlia; Genta, Fernando Ariel; Santiago, Marcelo Felippe; Coutinho-Silva, Robson; Savio, Luiz Eduardo Baggio; Kurtenbach, Eleonora (Frontiers in Immunology, 2022)
The P2X7 receptor is a critical purinergic receptor in immune cells. Its activation was associated with cathepsin release into macrophage cytosol, suggesting its involvement in lysosomal membrane permeabilization (LMP) and leakage. Nevertheless, the mechanisms by which P2X7 receptor activation induces LMP and leakage are unclear. This study investigated cellular mechanisms associated with endosomal and lysosomal leakage triggered by P2X7 receptor activation. We found that ATP at 500 μM and 5 mM (but not 50 μM) induced LMP in non-stimulated peritoneal macrophages. This effect was not observed in P2X7-deficient or A740003-pretreated macrophages. We found that the P2X7 receptor and pannexin-1 channels mediate calcium influx that might be important for activating specific ion channels (TRPM2 and two-pore channels) on the membranes of late endosomes and lysosomes to LMP leakage and consequent cathepsin release. These findings suggest the critical role of the P2X7 receptor in inflammatory and infectious diseases via lysosomal dysfunction.